2023
DOI: 10.15587/1729-4061.2023.280355
|View full text |Cite
|
Sign up to set email alerts
|

Development of a method for the search of solutions in the sphere of national security using bio-inspired algorithms

Volodymyr Koval,
Andrii Shyshatskyi,
Ruslan Ransevych
et al.

Abstract: The object of research are decision support systems. The subject of research is the decision-making process in management problems using bio-inspired algorithms. A method for the search of solutions in the field of national security using bio-inspired algorithms is proposed. The proposed method is based on a combination of an artificial bat algorithm and evolving artificial neural networks. The method has the following sequence of actions: ‒ input of initial data; ‒ processing of initial data taking into accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In vivo studies have shown that the stimulatory effect of resveratrol on SIRT1 is mediated by the activation by resveratrol of adenosine monophosphate activated protein kinase (AMPK), one of the key regulators of intracellular metabolism [38].…”
Section: Referencesmentioning
confidence: 99%
“…In vivo studies have shown that the stimulatory effect of resveratrol on SIRT1 is mediated by the activation by resveratrol of adenosine monophosphate activated protein kinase (AMPK), one of the key regulators of intracellular metabolism [38].…”
Section: Referencesmentioning
confidence: 99%
“…The concept of hybrid war turned out to be theoretically and practically the most suitable for determining the specifics of the actions of the Russian Federation (RF), which is trying to achieve its political aims by combining military, quasi-military, diplomatic, informational, economic and other ways. The specificity of the Russian hybrid aggression against Ukraine lies not so much in the general methods of hybrid warfare, but in Russia's unconditional violation of the system of international legal agreements, the large scale of the damage caused and the significant duration of the conflict [3][4][5]. In addition to the above mentioned, it is necessary to note the intensive conduct of hybrid actions by the enemy in the maritime environment since 2014 in order to prevent Ukraine from conducting economic activities at sea.…”
Section: Introductionmentioning
confidence: 99%